Novel mutations of the PRKAR1A gene in patients with acrodysostosis. (21st February 2013) - Muhn, F; Klopocki, E; Graul‐Neumann, L; Uhrig, S; Colley, A; Castori, M; Lankes, E; Henn, W; Gruber‐Sedlmayr, U; Seifert, W; Horn, D
Abstract : Acrodysostosis is characterized by a peripheral dysostosis that is accompanied by short stature, midface hypoplasia, and developmental delay. Recently, it was shown that heterozygous point mutations in the PRKAR1A gene cause acrodysostosis with hormone resistance. By mutational analysis of the PRKAR1A gene we detected four different mutations (p.Arg368Stop, p.Ala213Thr, p.Tyr373Cys, and p.Arg335Cys) in four of seven affected patients with acrodysostosis. The combination of clinical results, endocrinological parameters and in silico mutation analysis gives evidence to suppose a pathogenic effect of each mutation. This assumption is supported by the de novo origin of these mutations. Apart from typical radiological abnormalities of the hand bones, elevated thyroid stimulating hormone and parathyroid hormone values as well as short stature are the most common findings. Less frequent features are characteristic facial dysmorphisms, sensorineural hearing loss and mild intellectual disability. These results lead to the conclusion that mutations of PKRAR1A are the major molecular cause for acrodysostosis with endocrinological abnormalities. In addition, in our cohort of 44 patients affected with brachydactyly type E (BDE) we detected only one sequence variant of PRKAR1A (p.Asp227Asn) with an unclear effect on protein function. Thus, we conclude that PRKAR1A mutations may play no major role in the pathogenesis of BDE.